Regulation Involved in Colonization of Intercellular Spaces of Host Plants in Ralstonia solanacearum - Hikichi, Yasufumi; Mori, Yuka; Ishikawa, Shiho; Hayashi, Kazusa; Ohnishi, Kouhei; Kiba, Akinori; Kai, Kenji (Frontiers in Plant Science, 2017)
A soil-borne bacterium Ralstonia solanacearum invading plant roots first colonizes the intercellular spaces of the root, and eventually enters xylem vessels, where it replicates at high levels leading to wilting symptoms. After invasion into intercellular spaces, R. solanacearum strain OE1-1 attaches to host cells and expression of the hrp genes encoding components of the type III secretion system (T3SS). OE1-1 then constructs T3SS and secrets effectors into host cells, inducing expression of the host gene encoding phosphatidic acid phosphatase. This leads to suppressing plant innate immunity. Then, OE1-1 grows on host cells, inducing quorum sensing (QS). The QS contributes to regulation of OE1-1 colonization of intercellular spaces including mushroom-type biofilm formation on host cells, leading to its virulence. R. solanacearum strains AW1 and K60 produce methyl 3-hydroxypalmitate (3-OH PAME) as a QS signal. The methyltransferase PhcB synthesizes 3-OH PAME. When 3-OH PAME reaches a threshold level, it increases the ability of the histidine kinase PhcS to phosphorylate the response regulator PhcR. This results in elevated levels of functional PhcA, the global virulence regulator. On the other hand, strains OE1-1 and GMI1000 produce methyl 3-hydroxymyristate (3-OH MAME) as a QS signal. Among R. solanacearum strains, the deduced PhcB and PhcS amino acid sequences are related to the production of QS signals. R. solanacearum produces aryl-furanone secondary metabolites, ralfuranones, which are extracellularly secreted and required for its virulence, dependent on the QS. Interestingly, ralfuranones affect the QS feedback loop. Taken together, integrated signaling via ralfuranones influences the QS, contributing to pathogen virulence.